2009
DOI: 10.1016/j.pbb.2009.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C reduces spatial learning deficits in middle-aged and very old APP/PSEN1 transgenic and wild-type mice

Abstract: Alzheimer's disease is a progressive and fatal neurodegenerative disease characterized by a build up of amyloid β (Aβ) deposits, elevated oxidative stress, and deterioration of the cholinergic system. The present study investigated short-term cognitive-enhancing effects of acute intraperitoneal (i.p.) Vitamin C (ascorbate) treatment in APP/PSEN1 mice, a mouse model of Alzheimer's disease. Middle-aged (12 months) and Very old (24 months) APP/PSEN1 bigenic and wild-type mice were treated with ascorbate (125 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 48 publications
6
74
1
3
Order By: Relevance
“…In contrast to the study that used α-lipoic acid, vitamin C, when administered to other transgenic lines, such as APP/PSEN1 mice, did not decrease enhanced MDA levels in the cortex or Aβ plaque deposits in the cortex and ↑ increase, ↓ decrease, Ø no change, AGEs advanced glycation end products, GSH glutathione, PC protein carbonyl, TAC total antioxidant capacity hippocampal regions in either middle-aged or aged animals [252], although the drug administration improved memory, according to tests that suggested that cognitive rescue was achieved, to some degree, even in animals that suffered from severe neuropathology. The lack of effect of vitamin C on Aβ plaque deposits seems to result from the late introduction of medication in this test because Aβ plaques, considered an end point in the disease process, are detectable in these mice at 4-5 months, which was before the beginning of the test [252].…”
Section: Pharmacotherapeutic Strategy To Reduce Oscontrasting
confidence: 77%
See 1 more Smart Citation
“…In contrast to the study that used α-lipoic acid, vitamin C, when administered to other transgenic lines, such as APP/PSEN1 mice, did not decrease enhanced MDA levels in the cortex or Aβ plaque deposits in the cortex and ↑ increase, ↓ decrease, Ø no change, AGEs advanced glycation end products, GSH glutathione, PC protein carbonyl, TAC total antioxidant capacity hippocampal regions in either middle-aged or aged animals [252], although the drug administration improved memory, according to tests that suggested that cognitive rescue was achieved, to some degree, even in animals that suffered from severe neuropathology. The lack of effect of vitamin C on Aβ plaque deposits seems to result from the late introduction of medication in this test because Aβ plaques, considered an end point in the disease process, are detectable in these mice at 4-5 months, which was before the beginning of the test [252].…”
Section: Pharmacotherapeutic Strategy To Reduce Oscontrasting
confidence: 77%
“…MDA, HNE, or TBARS were enhanced in all of those models in the cerebral cortex or/and hippocampus or/and the whole brain [237][238][239][240][241][247][248][249][250][251][252][253][254][255]. Oxidative modification of proteins has also been demonstrated in the cortex and whole brain homogenate of transgenic AD mice [253,255] and in the cerebral cortex and hippocampus of an Aβ 1-42 mouse model [247].…”
Section: Animal Studiesmentioning
confidence: 99%
“…Sections were floated in 24-well plates containing 1xPBS and then mounted on gelatin-coated, charged glass slides. Three to five sections per mouse, containing hippocampus and cortex and spaced approximately 100 microns apart were chosen for quantification of thioflavin-S (Sigma Aldrich, USA) positive plaques as described previously 8, 71 . Digital images of the hippocampus and overlying cortex were taken using a fluorescent imaging microscope (EVOSfl, AMGmicro) at a magnification of 4X.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a randomized control trial by Li et al showed co-supplementation of Vitamin E and C with β-carotene (another well-established dietary antioxidant) markedly improved cognitive function in otherwise healthy elderly individuals [48]. Consistent with these clinical findings, an animal study reported that acute treatment with Vitamin C attenuates the spatial learning and memory in APP/PSEN1 transgenic AD model mice and also in aged none-AD wild-type mice [49]. However, in the same study, supplementation of Vitamin C did not alter cerebral redox state, inflammation and amyloidosis, indicating that the anti-dementia effects of vitamins may not only be attributed to its anti-oxidative properties.…”
Section: Antioxidants Cognitive Decline and Blood-brain Barriermentioning
confidence: 95%